Understanding the linkages between climate change and inequality in the United States - Ruchi Avtar; Kristian Blickle; Rajashri Chakrabarti; Janavi Janakiraman; Maxim Pinkovskiy (Federal Reserve Bank of New York, 2021)
We conduct a review of the existing academic literature to outline possible links between climate change and inequality in the United States. First, researchers have shown that the impact of both physical and transition risks may be uneven across location, income, race, and age. This is driven by a region's geography as well as its adaptation capabilities. Second, measures that individuals and governments take to adapt to climate change and transition to lower emissions risk increasing inequality. Finally, while federal aid and insurance coverage can mitigate the direct impact of physical risks, their structure may- inadvertently - sustain and entrench existing inequalities. We conclude by outlining some directions for future research on the nexus between inequality and climate change.
Keywords: Q54; Q58; D63; 330; climate; natural disaster; inequality